2021
DOI: 10.3390/molecules26071817
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Potential Markers of Glomerulopathy in Urine by HS-SPME-GC×GC TOFMS

Abstract: Volatile organic compounds (VOCs) exiting in urine are potential biomarkers of chronic kidney diseases. Headspace solid phase microextraction (HS-SPME) was applied for extraction VOCs over the urine samples. Volatile metabolites were separated and identified by means of two-dimensional gas chromatography and time of flight mass spectrometry (GC × GC TOF MS). Patients with glomerular diseases (n = 27) and healthy controls (n = 20) were recruited in the study. Different VOCs profiles were obtained from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In rat experiments, Meinardi et al found that the content of 2-pentanone in the breath of rats with chronic kidney disease and acute kidney injury induced by surgery was higher than that of control group. In human disease research, compared with healthy people, 2-pentanone is higher in urine of patients with glomerular disease and idiopathic membranous nephropathy . The increased content of 2-pentanone in breath and urine may be due to abnormal metabolism in the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…In rat experiments, Meinardi et al found that the content of 2-pentanone in the breath of rats with chronic kidney disease and acute kidney injury induced by surgery was higher than that of control group. In human disease research, compared with healthy people, 2-pentanone is higher in urine of patients with glomerular disease and idiopathic membranous nephropathy . The increased content of 2-pentanone in breath and urine may be due to abnormal metabolism in the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…Headspace GC analyzes only the vapor phase above the sample; thus, the additional derivatization stage is unnecessary. Metabolite concentrations in the vapor phase are low, and thus high sensitivity and mass resolution time-of-flight mass spectrometry (TOF-MS) is chosen [ 36 , 37 ]. The derivatization step can also help overcome low sensitivity and enhance signals.…”
Section: Analytical Methods In Ckd Metabolomics Studiesmentioning
confidence: 99%
“…Furthermore, resolution and sensitivity enhancement could be achieved by different MS instrumentation. The prevalent amount of CKD metabolomic works were made using time-of-flight mass spectrometry (TOF-MS) [ 23 , 36 , 39 , 42 ] and quadrupole time-of-flight mass spectrometry (Q-TOF-MS) [ 43 , 44 , 45 , 46 ], which is characterized by high sensitivity, fast scanning speeds, and accurate mass measurements. However, in one of the works, both Q-TOF-MS and reconstitution techniques were performed [ 40 ].…”
Section: Analytical Methods In Ckd Metabolomics Studiesmentioning
confidence: 99%
“…SPME extraction, desorption, and thermal fiber cleaning were carried out automatically by means of an MPS-2 autosampler. The fiber and sample conditions were applied according to those utilized in earlier experiments [ 32 ].…”
Section: Methodsmentioning
confidence: 99%